Climatic Drivers of Deglacial SST Variability in the Eastern Pacific. Issue 10 (5th October 2021) - Meegan Kumar, Dervla; Tierney, Jessica E.; Bhattacharya, Tripti; Zhu, Jiang; McCarty, Logan; Murray, James W.
Abstract: We explore the response of northeastern Pacific sea surface temperature (SST) to deglacial ( ∼ 16–7 ka) climate variability as recorded in U 37 K ′ ‐based SST reconstructions spanning 65°N to 10°S. Included in the analysis is a new 23 kyr SST record from core NH8P from the northwest Mexican Margin. We isolate spatiotemporal patterns in regional SSTs with trend empirical orthogonal function (TEOF) analysis. The dominant TEOF mode reflects deglacial warming associated with rising p C O 2 . Tropical and subtropical SSTs correlated most strongly with this mode, suggesting that the thermodynamic response of the tropical eastern Pacific to greenhouse gas forcing was the dominant driver of regional SST change during deglaciation. The second TEOF mode reflects millennial‐scale variability and is most strongly expressed in subpolar SSTs. The synchronous timing between North Pacific and North Atlantic SST oscillations is evidence for the rapid transmission of millennial‐scale climate perturbations between the basins, likely through an atmospheric teleconnection. SSTs at NH8P have no correlation with either leading TEOF mode as there is minimal change in SST at this site after ∼ 20 ka. A model simulation of the LGM indicates that glacial cooling was muted in much of the Eastern Pacific Warm Pool (EPWP), in which NH8P lies, due to reductions in latent heat flux. This suggests that the wind‐evaporation‐SST feedback was responsible for the attenuation of EPWP cooling. Overall, this study highlights the distinct latitudinal trends in the Pacific's response to deglaciation. Key Points: A new U 37 K ′ record from the northwest Mexican Margin shows minimal sea surface temperature (SST) change across the last deglaciation Trend empirical orthogonal function analysis identifies mechanisms behind deglacial patterns of northeastern Pacific SST variability Wind‐evaporation‐SST feedback important for mitigating deglacial warming in the Eastern Pacific Warm Pool